Did Lockdown Work? An Economist's Cross-Country Comparison. (29th March 2021) - Bjørnskov, Christian
Abstract: I explore the association between the severity of lockdown policies in the first half of 2020 and mortality rates. Using two indices from the Blavatnik Centre's COVID-19 policy measures and comparing weekly mortality rates from 24 European countries in the first halves of 2017–2020, addressing policy endogeneity in two different ways, and taking timing into account, I find no clear association between lockdown policies and mortality development.